2018
DOI: 10.4269/ajtmh.17-0667
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Fogarty International Center-Supported Tuberculosis Research Training Program in the Country of Georgia

Abstract: In 2004, there existed limited tuberculosis (TB) research capacity in the country of Georgia. In response, a collaborative research training program (RTP) supported by a National Institutes of Health Fogarty International Center Global Infectious Diseases grant was formed between a U.S. academic institution and the National Center for Tuberculosis and Lung Disease (NCTLD) and other institutions in Georgia. We sought to assess outcomes of this RTP. The TB RTP combined didactic and mentored research training for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…Our assessment is consistent with most of the earlier program evaluations, which focused on individual research training outcomes in terms of publications, conference presentations, successful grant applications, qualifications obtained, and dissemination of study results [11,[23][24][25][26][27][28][29], and for institutional capacity strengthening, the number of workshops and training activities at institutes [30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our assessment is consistent with most of the earlier program evaluations, which focused on individual research training outcomes in terms of publications, conference presentations, successful grant applications, qualifications obtained, and dissemination of study results [11,[23][24][25][26][27][28][29], and for institutional capacity strengthening, the number of workshops and training activities at institutes [30].…”
Section: Discussionsupporting
confidence: 81%
“…Measuring institutional research capacity strengthening is more challenging [27]. The knowledge gained by the beneficiaries needs to be shared and disseminated.…”
Section: Discussionmentioning
confidence: 99%
“…This increase is attributed in large part to an expansion of research activity and therefore opportunities at the NCTLD, including ongoing clinical trials of new anti-tuberculosis drugs, and a National Institutes of Health Fogarty International Center Global Infectious Diseases (Bethesda, MD, USA) programme. 28 While we did not find an association between involvement in research and overall satisfaction, only 18% of respondents reported being involved in research activities. Broadening the scope of practice of NTP physicians to include more general pulmonary disease could facilitate a greater variety of career options, as has been suggested for the specialisation of infectious diseases in the United States.…”
Section: Discussioncontrasting
confidence: 60%
“…50 Graduates of such programs gain requisite skills to conduct meaningful research that influences national and global policies and go on to receive further funding. 51,52 Mutual understanding of local context may allow for more sustainable and understanding academic global health collaborations.…”
Section: Discussionmentioning
confidence: 99%